Yam in the home - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Yam can be grown anywhere: even downtown, on paved roofs, terraces, balconies and ? why not? ? in the living room. In Cameroon, for example, a clever do-it-yourselfer senior citizen of some sixty odd years has developed an original method of growing...